RETRACTED: LINC00174 Facilitates Cell Proliferation, Cell Migration and Tumor Growth of Osteosarcoma via Regulating the TGF-β/SMAD Signaling Pathway and Upregulating SSH2 Expression - Zheng, Changjun; Li, Ronghang; Zheng, Shuang; Fang, Hongjuan; Xu, Meng; Zhong, Lei (Frontiers in Molecular Biosciences, 2021)
Osteosarcoma (OS), a frequent malignant tumor which mainly occurs in the bone. The roles of long noncoding RNAs (lncRNAs) have been revealed in cancers, including OS. LncRNA long intergenic non-protein coding RNA (LINC00174) has been validated as an oncogene in several cancers. However, the role of LINC00174 in OS has not been explored. In our research, loss-of-function assays were conducted to explore the function of LINC00174 in OS cells. Then, we explored the downstream pathway of LINC00174 in OS cells. Bioinformatics, RNA pull-down and RIP experiments investigated the downstream mechanism of LINC00174 in OS cells. Finally, in vivo assays clarified the effect of LINC00174 on tumorigenesis. We found that LINC00174 was upregulated in OS tissues and cells. LINC00174 knockdown repressed OS cell growth. Mechanistically, LINC00174 knockdown suppressed the TGF-β/SMAD pathway. LINC00174 interacted with miR-378a-3p, and slingshot protein phosphatase 2 (SSH2) 3’UTR was targeted by miR-378a-3p in OS cells. Rescue assays showed that SSH2 upregulation or miR-378a-3p inhibition counteracted the inhibitory effect of LINC00174 depletion in OS cell growth. Additionally, LINC00174 depletion suppressed tumor growth in mice. In conclusion, LINC00174 promotes OS cellular malignancy and tumorigenesis via the miR-378a-3p/SSH2 axis and the TGF-β/SMAD pathway, which might provide a novel insight for OS treatment.